A Study of Elders’ Health Status and Perception about Old Age - Timalsina, Keshab Prasad (International Research Journal of MMC, 2021)
The health status of elders and elders’ perception regarding old age in a community is an important issue in a society. The present study aims to assess the health status and perception of old age of elderly population of Nijgadh Municipality. A descriptive cross-sectional study has been carried out among 204 elders taken from the community through simple random sampling method. The data were collected through face to face structured interview schedule in 2021. The descriptive and inferential statistical analysis of the collected data showed that the about 20 percent elders had got good status of health but remaining (about 80%) of them were suffering from  some kinds of health complications. Similarly, more than 73 percent of elders felt their life more problematic. This study measured significant variation (p